التعلم ألمنظمي وأثره في نجاح المنظمات دراسة ميدانية في شركات وزارة الأعمار والإسكان في العراق - الكبيسي, صلاح الدين عواد; دهام, عبد الستار ابراهيم (Journal of Economics and Administrative Sciences, 2007)
The world witness quality jumps under radical change in the management and work styles, through adopting organizational learning as a process of continuous improvements in response to environmental stimulus, in the knowledge age and turbulent competitive environment the organizational success concept is shift from the view narrow for financial performance and marketshare to long term view which focus on building strategic capabilities that provide a sustainable competitive advantage.Considering the strategic role assumed for the companies of the Ministry of Construction and Housing to play it, these companies have been chosen to be the field in which questions of this study will be tested.These questions concern the nature of level and influence of the organizational learning and organizational’s success. The aim of this study is to answer these questions. Data collected principally by questionnaire tool from a sample of (66) managers. Results proved that companies have acceptable level of organizational learning and success; organizational learning has significant influence in companies success.